... ikke blot ved siden af Thronen, men højere end Thronen. Ludvig Holstein-Ledreborg og Folketingsparlamentarismen - Wendel-Hansen, Jens Lei (Historisk Tidsskrift, 2014)
Ludvig Holstein-Ledreborg and the Constitutional Struggle Like his peers among major Danish landowners count Ludvig Holstein- Ledreborg (1839-1912) took a firm stand against parliamentary government when Venstre [literally: »the Left«, a major party with progressive attitudes that represented the rural population] in 1873 demanded that the king choose a government backed by a majority in the Danish second chamber, Folketinget. Nevertheless – unlike most others in his social position, who were typically Conservative – Holstein-Ledreborg joined Venstre in 1875 and soon became a leading figure. No internal conflict arose on that account, for the essence of the constitutional struggle during the Estrup administration 1875-94 was not the question of whether to adapt a parliamentary system of government or not. The core issue for the opposition was to secure the legislative power of Folketinget as stipulated by the constitution. The government circumvented this rule by provisional budgets not endorsed by parliament. Holstein-Ledreborg firmly dismissed the notion that the real intention of the opposition when advancing the claim in 1873 had been to make the government dependent on the approval of Folketinget alone instead of being appointed by and held accountable to the king. Indeed, when Holstein-Ledreborg left Danish politics in 1890, he felt it was urgent to make clear once again that he was strictly against parliamentary government. What he favoured and had always fought for was cooperation between the two chambers and between these and the king’s government in order to include the whole nation in political affairs and maintain equilibrium in the polity. By implication, Holstein-Ledreborg did not necessarily or even probably long for democratization of the first chamber, Landstinget, which since 1866 was elected by unequal suffrage, favouring the landowners. Arguing against such a reform during the election campaign of 1913, Holstein-Ledreborg’s son claimed to be in agreement with the views of his late father on this matter. The analysed case suggests that the protracted struggle over the constitution in Denmark is not adequately defined by the cleavage between liberal democrats and conservative provisionalists alone. Over long periods, the moderate factions in Venstre, Holstein-Ledreborg being one of the leaders, did not call for demo cratizing the constitution, but for holding it in respect in its entirety, including but not restricted to Folketinget.